Designing strategies for integrated control of ticks and tick-borne diseases at the farm level in a mixed crop-livestock system in Uganda - Sakwa, P.D.; Randolph, Thomas F.; Opuda-Asibo, J.; Otim, C.P. (International Society for Veterinary Epidemiology and Economics, 2000)
Ticks and tickborne diseases (TTBD) are serious animal health constraints in Uganda and acaricides are the current method of choice for their control. Although widely used, the external-input, single-technology paradigm of chemical control is unsustainable and may inhibit endemic stability. TTBD control could benefit from ecologically-based integrated pest management (IPM), which relies heavily on renewable resources administered in an integrated manner, natural mortality factors and control tactics that disrupt these factors as little as possible. Based on information generated during a preliminary survey, this paper outlines a fiamework for designing IPM strategies for TTBDs.